Monitoring Analysis of the Apron Movement Control Unit (AMC) on Bus Maneuvering in the Airside Area during Hajj Flights at Adi Soemarmo Boyolali Airport - Amarta Lutfi Nurrohyani; Elnia Frisnawati (CV. Rayyan Dwi Bharata, 2023)
Adi Soemarmo Boyolali Airport is one of the airports used for Hajj departures. There are so many pilgrims who make movements in the airside area, a lot of supervision is required for the maneuvering of buses and pilgrims. This activity forced the AMC unit to carry out surveillance in the airside area. Because the airside area is an area that not everyone can enter without permission from the airport. This study uses a qualitative method. Data collection techniques in this study were in the form of observation, interviews, and documentation. The techniques in analyzing the research data are in the form of data reduction, data presentation, conclusion drawing, and data validity. This supervision is carried out on buses and passengers who will make pilgrimage flights, so that operations run smoothly and regularly. Obstacles in the supervision of the Apron Movement Control (AMC) unit towards maneuvering buses in the Airside area during Hajj flights at Adi Soemarmo Boyolali Airport are related to weather factors and the lack of knowledge of passengers about the rules in the Airside area.